Effect of sintering temperature on the morphology, crystallinity and mechanical properties of carbonated hydroxyapatite (CHA). Issue 17 (1st December 2020) - Safarzadeh, M.; Chee, Chin Fei; Ramesh, S.; Fauzi, M.N. Ahmad
Abstract: Effect of sintering temperature on the physical and mechanical properties of synthesized B-type carbonated hydroxyapatite (CHA) over a range of temperature in CO2 atmosphere has been investigated. The B-type CHA in nano size was synthesized at room temperature by using a direct pouring wet chemical precipitation method. The synthesized CHA powders were subsequently consolidated by sintering treatment from 800 to 1100 °C. The sintered CHA samples were evaluated using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectrometry, X-ray fluorescence (XRF), carbon-hydrogen-nitrogen-sulfur-oxygen (CHNS/O) elemental analyzer, Field emission scanning electron microscopy (FESEM), and Vicker's indentation technique. The results obtained from XRD and FESEM indicated that the synthesized B-type CHA powders were nanometer in size. The crystallinity and crystallite size of the sintered CHA samples were increased due to increasing sintering temperature. The heat treatment between 800 °C and 1000 °C has resulted in coarsening and increased hardness of the sintered CHA samples. However, these properties began to deteriorate when sintering beyond 1100 °C due the formation of calcium oxide.